Upaya dalam Menumbuhkan Karakter Agamis Siswa pada Bulan Suci Ramadhan di Madrasah Tsanawiyyah Negeri Binjai - Febri Nanda Monalisa; Rizki Akmalia; Alwi Shihab Syah Harahap; Putri Febby Aulia (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Many students at this time are starting to leave the cultural traditions of the Indonesian nation and leave moral norms that cannot be separated from the importance of growing the religious character of students in schools in the teaching and learning process in the classroom. Therefore, so that students have characters that are in accordance with norms and religion, it is hoped that schools can foster a culture, one of which is by carrying out positive activities during the holy month of Ramadan. The researcher formulated the objectives of this study to: (1) The activities carried out during the holy month of Ramadan to cultivate the religious character of students at MTsN Binjai, (2) How did the activities carried out during the holy month of Ramadan at MTsN Binjai, (3) Inhibitory factors and supporters of carrying out activities during the holy month of Ramadan at MTsN Binjai. This type of research is qualitative, with the principal research subject. And data collection was done by interview and field observation with relevant themes. The results of this study indicate that: (1) The forms of activities carried out to cultivate the religious character of students in the month of Ramadan are dhuha prayer in congregation, almsgiving, tausiyah, and tadarus (2) There is an influence from these activities which makes students' awareness higher to carry out worship and have a noble character (3) Supporting factors come from facilities and cooperation carried out by the school (4) Inhibiting factors originating from students are overcome by reminding them to always be disciplined.